EMPOWERING TEACHERS: EXPLORING THE BALANCE BE-TWEEN ENGAGEMENT AND BURNOUT - Ausra Rutkiene (PUPIL: International Journal of Teaching, Education and Learning, 2026)
Teacher well-being is conceptualized as a multidimensional construct, encompassing both positive (job satisfaction, engagement) and negative dimensions (stress, burnout). Dissatisfied teachers exhibit lower motivation, reduced classroom performance, and higher turnover rates. Job dissatisfaction stems from poor working conditions, insufficient pay, and lack of professional development support. Work engagement combines vigor, dedication, and absorption, leading to higher commitment and energy in teaching tasks. Self-efficacy reflects teachers’ confidence in their ability to manage classrooms, motivate students, and achieve teaching goals. Stress, a common issue in teaching, is heightened by policy changes, challenging student behavior, and inadequate support from school administration. Chronic stress can lead to burnout, marked by exhaustion, cynicism, and feelings of inadequacy. The study analyzed data from 427 teachers collected between September and October 2023. Stress was measured using the Perceived Stress Scale (PSS), assessing the intensity and impact of work-related stress. Burnout was evaluated with the Bergen Burnout Inventory (BBI), focusing on exhaustion, cynicism, and reduced professional efficacy. Self-efficacy was measured based on teachers’ skills in instruction, student motivation, discipline, and collaboration. Work engagement was assessed using the Utrecht Work Engagement Scale, emphasizing energy, dedication, and focus. Results revealed an average stress score of 23.26 (out of 40), with variations based on teaching experience. Burnout levels were higher among mid-career teachers (11–20 years of service), particularly in exhaustion. Teachers with higher self-efficacy experienced significantly lower burnout levels, regardless of career stage. High work engagement correlated with reduced burnout, showcasing the protective role of dedication and vigor. Teachers’ stress and burnout negatively impact their relationships with students, classroom climate, and student learning outcomes. The study underscores the need for schools to enhance teacher support systems and professional development opportunities. Promoting self-efficacy and engagement is essential to mitigating stress, preventing burnout, and ensuring teacher retention.